Are we all in this together?: mathematics teachers' perspectives on equity in remote instruction during pandemic - GÜLBAĞCI DEDE, HANDE (SPRINGER, 2021)
The COVID-19 pandemic is an unprecedented situation that influenced all aspects of society, including education. Millions of students found themselves adjusting to a new medium of mathematics instruction, not to mention the teachers who had to provide instruction through remote sources. Considering students' diverse social, economic, and academic background, this study sought to examine teachers' perspectives on factors that support or hinder how equity is attended to in mathematics during remote instruction and the extent it differed from practices utilized when instruction was provided in a face-to-face setting. We also sought to document teachers' perspectives on how they attended to equity in mathematics to support students with language barriers. We interviewed nine teachers to explore their perspectives of factors that support or hinder equity in mathematics teaching and learning during remote instruction compared to face-to-face instruction and how they support the diverse needs (inclusive of language barriers) of students. There were salient factors in this study that supported or hindered equitable mathematics instruction, such as teachers' beliefs, expectations for students, access to resources, students' socioeconomic status, and language barriers. Hence, it is recommended that policymakers, school administrators, and teachers need to collaborate to systematically plan to ensure that all students have access to quality mathematics.
Keywords: Accessibility; COVID-19; Equitable mathematics instruction; Language barrier; Socioeconomic status; TECHNOLOGY; CURRICULUM; EDUCATION; TURKEY; ACCESS